Design, Synthesis and Characterisation of Novel Phenothiazine‐Based Triazolopyridine Derivatives: Evaluation of Anti‐Breast Cancer Activity on Human Breast Carcinoma. Issue 43 (26th November 2019) - Sachdeva, Tanisha; Low, May Lee; Mai, Chun‐Wai; Cheong, Siew Lee; Liew, Yun Khoon; Milton, Marilyn Daisy
Abstract: A series of novel phenothiazine based [ 1, 2, 4 ]triazolo[ 4, 3 ‐ a ]pyridine scaffolds were designed and synthesized in good yields by the oxidative cyclisation of phenothiazine pyridylhydrazones. Biological responses of all compounds toward a panel of human breast cancer cells (MDA‐MB‐231, MDA‐MB‐468, MCF7, SKBR3 and T47D) and human non‐tumorigenic epithelial breast cells (MCF10 A) were evaluated. Structure‐activity relationship revealed that compound with pendant phenyl ring on phenothiazine exhibited significant cytotoxic activity and apoptotic induction effects against breast cancer cell line with IC50 value 10.2 to 17.6 μM. Notably, the cytotoxic effect was 3.5 fold higher on cancer than non‐cancer cells, indicating potential control of breast cancer with lower side effects. Molecular docking studies confirmed the presence of hydrophobic contacts between appended phenyl ring, triazolopyridine and phenothiazine moieties with adjacent residues within the binding pocket of tubulin. One of the nitrogen in the triazolo ring also showed hydrogen bonding with tubulin. These tubulin interactions were also found with the taxane ring of paclitaxel. Cell cycle analysis confirmed the G2/M arrest induced by this compound on human breast cancer cells. Therefore, the potential anti‐cancer, pro‐apoptotic, and cell cycle arrest warrant further development of this molecule as a new class of anticancer agent. Abstract : In an effort to develop a new class of anticancer agent, a series of novel phenothiazine‐triazolopyridine scaffolds were synthesized. One of the compounds exhibited significant cytotoxic activity and apoptotic induction effect against breast cancer cells with IC50 value 10.2 ±3.5 μM. The cytotoxic effect indicated potential control of breast cancer with lower side effects. Molecular docking studies revealed interactions within compound and tubulin. Cell cycle analysis confirmed the G2/M arrest on human breast cancer cells.